A237 COLONOSCOPY PREPARATION OPTIMIZATION FOR INPATIENTS (COIN STUDY). A RANDOMIZED CONTROLLED TRIAL COMPARING 4L PEGLYTE TO REGULAR DOSE PICO SALAX AND SPLIT DOSE PICO SALAX FOR COLONOSCOPY BOWEL PREPARATION IN HOSPITALIZED PATIENTS. (1st March 2018) - Khan, K; Merali, A; Forbes, N; Fergani, H; Ganguli, S; Jalali, S; Spaziani, R; Tsoi, K; Morgan, D
Abstract: Background: Colonoscopy is routinely performed in hospitalized patients (HP) for investigation and treatment. Being a HP is a risk factor for a poor bowel preparation but there are limited studies examining bowel cleansing in this population. Aims: Our goal was to determine whether a low volume prep (PicoSalax) taken the day before or as a split prep is superior to a 4L of PegLyte taken the day before colonoscopy. Methods: This single-centre, endoscopist-blinded, three armed randomized controlled trial compared 4L PEG-Lyte to regular dose Pico Salax and to split dose Pico-Salax for colonoscopy preparation in HP's. In addition, all patients were given Bisacodyl before starting the preparation. Inclusion criteria: Adult in-patients requiring colonoscopy. Exclusion criteria: renal insufficiency, severe congestive heart failure, recent myocardial infarction, ileus, ascites, severe colitis, megacolon, gastrointestinal obstruction, presence feeding tube, bowel resection, pregnancy, or allergy to study drugs. The primary outcome was overall cleansing efficacy using the Ottawa Bowel Preparation Scale (OBPS) as determined by the endoscopist. Secondary outcomes were components of the OBPS, canceled or repeated procedure due to poor cleansing, and safety and tolerability. The study sample size was calculated to be 126 patients. Results: From October 2012 to November 2016, 44 patients were recruited and randomized. One patient refused to take the preparation. One patient's procedure was canceled, and one patient was un-blinded due to poor response. The average patient age was 65.7 year's with 22 females (50%). Indications for colonoscopy include investigation of bleeding (18), anemia (13), change in bowels (6), and abnormal imaging (2). There were 16 patients in the Pico Salax day before group, with mean OBPS of 6.5 (standard deviation (SD) 3.4), 13 patients in the Pico Salax split dose group, with mean OBPS of 4.3 (SD 2.6), and 15 patients in the PEGLyte group, with mean OBPS of 4.9 (SD 2.9) with ANOVA showing no difference between groups (p=0.15). Four patients reported severe adverse effects while taking the prep. Bowel preparation did not result in any cancelation or repeat procedure. The study was terminated early due to poor recruitment. Conclusions: Preparing hospitalized patients for colonoscopy is a challenging task. The optimal bowel preparation for these patients remains unknown. This study did not show any meaningful difference between groups taking PicoSalax the day before colonoscopy, or Pico Salax as a split preparation, or PEG Lyte the day before colonoscopy but was limited in power because of poor recruitment. Further research is needed in this population. Funding Agencies: Resident Research Grant, Department of Medicine, McMaster University.